Characterization of Small Renal Tumors With Magnetic Resonance Elastography: A Feasibility Study. Issue 6 (June 2018) - Prezzi, Davide; Neji, Radhouene; Kelly-Morland, Christian; Verma, Hema; O'Brien, Tim; Challacombe, Ben; Fernando, Archana; Chandra, Ashish; Sinkus, Ralph; Goh, Vicky
Abstract : Objectives: The aim of this study was to explore the feasibility of magnetic resonance elastography (MRE) for characterizing indeterminate small renal tumors (SRTs) as part of a multiparametric magnetic resonance (MR) imaging protocol. Materials and Methods: After institutional review board approval and informed consent were obtained, 21 prospective adults (15 men; median age, 55 years; age range, 25–72 years) with SRT were enrolled. Tumors (2–5 cm Ø) were imaged using 3-directional, gradient echo MRE. Viscoelastic parametric maps (shear wave velocity [ c ] and attenuation [ α ]) were analyzed by 2 independent radiologists. Interobserver agreement (Bland-Altman statistics and intraclass correlation coefficients) was assessed. Anatomical T2-weighted, dynamic contrast-enhanced (DCE) and diffusion sequences completed the acquisition protocol. Imaging parameters were compared between groups (Mann-Whitney U test). Results: Quality of MRE was good in 18 cases (mean nonlinearity <50%), including 1 papillary renal cell carcinoma and 1 metanephric adenoma. A cohort of 5 oncocytomas and 11 clear-cell renal cell carcinomas (ccRCCs) was analyzed for statistical differences. The MRE viscoelastic parameters were the strongest imaging discriminators: oncocytomas displayed significantly lower shear velocity c (median, 0.77 m/s; interquartile range [IQR], 0.76–0.79) ( P = 0.007) and higher shear attenuation α (median, 0.087 mm −1 ; IQR, 0.082–0.087) ( P = 0.008) than ccRCC (medians, 0.92 m/s and 0.066 mm −1 ; IQR, 0.84–0.97 and 0.054–0.074, respectively). T2 signal intensity ratio (tumor/renal cortex) was lower in oncocytomas ( P = 0.02). The DCE and diffusion MR parameters overlapped substantially ( P ≥ 0.1). Oncocytomas displayed a consistent MRE viscoelastic profile, corresponding to data point clustering in a bidimensional scatter plot. Values for MRE intraclass correlation coefficient were 0.982 for c and 0.984 for α, indicating excellent interobserver agreement. Conclusions: Magnetic resonance elastography is feasible for SRT characterization; MRE viscoelastic parameters were stronger discriminators between oncocytoma and ccRCC than anatomical, DCE and diffusion MR imaging parameters.